Improving nitrogen use efficiency of winter oilseed rape (Brasica napus L.) - Fraser, Alison (2021)
Nitrogen (N) fertilisers are used widely to improve winter oilseed rape (WOSR) yields. However, N is an expensive input and has environmental effects including greenhouse gas (GHG) emissions and nitrate leaching. Significant genetic variation in N use efficiency (NUE) has been reported among WOSR genotypes, and this can potentially be exploited by plant breeders. OSR yields are highly variable. They are affected by genetics, environment and agronomic practice as well as the interactions between them. Trials comparing NUE of diverse genotypes have shown that cultivar yields are ranked differently at high N and low N rates. If the interaction between genotype and N supply is highly significant but the correlation between low N and high N yields is low then it is possible to select genotypes with adaptations to low N. Better management of N application, with precise application rates dependent on genotype and environment, has the potential to improve NUE. In order to calculate the optimum N rate it is necessary to know both yield potential of the site and N requirements of the genotype, assuming the intention is to reduce N applications whilst maintaining yield (or to increase yields whilst maintaining N application). Therefore, understanding genotype performance over multiple environmental and management conditions is essential.